Effects of Field Fumigation and Inoculation With the Pecan Truffle (Tuber lyonii) on the Fungal Community of Pecan (Carya illinoinensis) Seedlings Over 5 Years - Grupe, Arthur C.; Jusino, Michelle A.; Mujic, Alija B.; Spakes-Richter, Brantlee; Bonito, Gregory; Brenneman, Tim; Smith, Matthew E. (Frontiers in Microbiology, 2021)
Truffle fungi are esteemed for their aromatic qualities and are among the most widely cultivated edible ectomycorrhizal fungi. Here we document a successful method for establishing Tuber lyonii, the pecan truffle, on pecan (Carya illinoinensis) seedlings in a field setting. We assessed the impacts of soil fumigation and varying concentrations of truffle spore inoculum on the ectomycorrhizal fungal and the complete fungal communities as well as the colonization of T. lyonii on pecan roots at three nurseries in Georgia, USA. To identify fungal communities on pecan seedlings, we performed high-throughput amplicon sequencing of the fungal ITS1 rDNA region. Our five-year long field experiment demonstrates that fumigation and inoculation together resulted in the highest persistence of T. lyonii on pecan roots. Fungal communities became more complex and diverse over time, such that older seedlings were less likely to be dominated by Tuber lyonii compared to younger ones, suggesting successional changes in the fungal community over time. This suggests that transplanting inoculated seedlings after two or three years post-inoculation is optimal for future truffle propagation efforts. Our results demonstrate that Tuber lyonii can be established in situ with methods that are compatible with current pecan nursery industry practices and that fungal communities on pecan seedlings vary depending on the experimental treatments used during planting. While the pecan truffle is not yet widely cultivated, our results provide insights for future large-scale cultivation of this and perhaps other gourmet ectomycorrhizal fungi.